A magyar energiapolitika geopolitikai aspektusai = Geopolitical aspects of hungary’s energy policy - Haffner, Tamás (Közép-Európai Közlemények, 2018)
Hungary is an extremely poor state in terms of energy resources; the energy policy of the country and the structure of energy resources used have been and are determined by the energy import dependence. After WWII, it could obtain its increased demand necessary to its extensive energyintensive industry established based on the Soviet model almost entirely from the Soviet Union. Hungary, just like other Central-European countries, tried to decrease its unilateral dependence on energy import linked to Russia through several measures in the past 25 years but these efforts achieved partial success only; the Russian energy import dependence of Hungary and of a large part of Central-Europe remained till the present days. The ‘National Energy Strategy 2030’ developed on the basis of the guideline, adopted in 2011, specified insurance of long-term sustainability, security and economic competitiveness as primary objective of the Hungarian energy policy. The Government intends to guarantee security of supply, to enforce environmental considerations and depending on the options of the country, to stand up for solving global problems through implementation of the strategy. The strategy intends to achieve the termination of the electricity import balance of the country until 2030 by this ‘Nuclear-Coal-Green’ scenario based on these three pillars.